2005
DOI: 10.1163/156854105774355563
|View full text |Cite
|
Sign up to set email alerts
|

Prey preference and feeding behaviour of the diplogastrid predator Mononchoides gaugleri (Nematoda: Diplogastrida)

Abstract: Prey preference and feeding behaviour of Mononchoides gaugleri were studied using 11 phytoparasitic nematode species as prey. A full range of prey preferences were detected in no choice and paired choice predator-prey experiments. Meloidogyne incognita, Heterodera mothi and Anguina tritici juveniles (coefficient of preference = 0.92-1.00) were highly preferred as prey by M. gaugleri in all tests. The second tier of prey preference was occupied by the adult Hirschmanniella oryzae, Tylenchorhynchus mashhoodi, Xi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…Earlier worker, have offered only limited number of preys (25 -50) in their experimentation that might have affected their results. They have also reported that the predation rate is affected by prey density (Yeates, 1969;Bilgrami & Jairajpuri, 1989;Bilgrami et al, 2005). Since F. composticola has high predation rate for both plant parasitic and fungivorous nematodes, biological potential of this nematode may be exploited for their management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier worker, have offered only limited number of preys (25 -50) in their experimentation that might have affected their results. They have also reported that the predation rate is affected by prey density (Yeates, 1969;Bilgrami & Jairajpuri, 1989;Bilgrami et al, 2005). Since F. composticola has high predation rate for both plant parasitic and fungivorous nematodes, biological potential of this nematode may be exploited for their management.…”
Section: Discussionmentioning
confidence: 99%
“…As with other diplogasterids, the life cycle of F. composticola is short and has high fecundity and is affected by temperature. It is a voracious feeder and its predation rate is much higher than reported for other diplogasterids (Yeates, 1969;Steel et al, 2011;Bilgrami et al, 2005). Earlier worker, have offered only limited number of preys (25 -50) in their experimentation that might have affected their results.…”
Section: Discussionmentioning
confidence: 99%
“…Predation rates can be influenced by prey density and by interference between different predators in the same habitat (Hamels et al, 2001). Yeates (1969), Bilgrami and Jairajpuri (1989) and Bilgrami et al (2005) demonstrated that Mononchoides species show prey density-dependent predation rates.…”
Section: Characterisationmentioning
confidence: 99%
“…detected and migrated to bacterial colonies and preyed upon bacterial-feeding nematodes. Several Mononchoides species have been reported as predators on other nematodes: M. potohikus (Yeates, 1969), M. longicaudatus (Bilgrami & Jairajpuri, 1988), M. fortidens (Bilgrami & Jairajpuri, 1988), M. gaugleri (Bilgrami et al, 2005), M. bollingeri (Goodrich et al, 1968) and M. changi (Goodrich et al, 1968). As demonstrated in Figure 5C and D, and as described by Bilgrami and Jairajpuri (1989) and Fürst von Lieven and Sudhaus (2000), Mononchoides species pierce the cuticle of their prey by using their movable dorsal tooth, in addition to pharyngeal suction.…”
Section: Characterisationmentioning
confidence: 99%
See 1 more Smart Citation